The Southern Cone model : the political economy of regional capitalist development in Latin America - Phillips, Nicola, 1971- (London ; New York : Routledge, 2004)
Developing an original blend of perspectives from the fields of international and comparative political economy, this book presents an innovative and in-depth account of the contemporary political economy of the southern cone of Latin America: Argentina, Brazil, Chile, Paraguay and Uruguay. It identifies a new and distinctive model of regional capitalist development emerging in the southern cone and a complex relationship with both the global political economy and the five distinctive national political economies in the region. Ranging across the contours of labour, business, states and.
The political economy of capitalist development -- Post-war development and regional integration -- Versions of neoliberalism -- The Mercosur project -- The reconfiguration of regionalist dynamics -- Labour -- Business -- States -- The Southern Cone model.
Includes bibliographical references (pages 271-296) and index.
Print version record.
English.
eBooks on EBSCOhost
Keywords: Capitalism -- Southern Cone of South America; Regional economics -- Case studies; Southern Cone of South America -- Economic conditions; Southern Cone of South America -- Economic policy; Économie régionale -- Études de cas; POLITICAL SCIENCE -- Public Policy -- Economic Policy; BUSINESS & ECONOMICS -- Government & Business; BUSINESS & ECONOMICS -- Development -- Economic Development; BUSINESS & ECONOMICS -- Development -- Business Development; BUSINESS & ECONOMICS -- Structural Adjustment; BUSINESS & ECONOMICS -- Development -- General; Capitalism; Economic history; Economic policy; Regional economics; South America -- Southern Cone of South America; Electronic books; Case studies